Genetic characterization of the Latvian local goat breed and genetic traits associated with somatic cell count - D. Gudra; A. Valdovska; D. Jonkus; D. Kairisa; D. Galina; M. Ustinova; K. Viksne; D. Fridmanis; I. Kalnina (Animal, 2024)
The Latvian local goat (LVK) breed represents the only native domestic goat breed in Latvia, but its limited population places it within the endangered category. However, the LVK breed has not yet undergone a comprehensive genetic characterization. Therefore, we completed whole genome sequencing to reveal the genetic foundation of the LVK breed while identifying genetic traits linked to the somatic cell count (SCC) levels. The study included 40 genomes of LVK goats sequenced to acquire at least 35x or 10x coverage. A Principal component analysis, a genetic distance tree, and an admixture analysis showed LVK's similarity to some European breeds, such as Finnish Landrace, Alpine, and Saanen, which aligns with the breed's history. An analysis of genome-wide heterozygosity, nucleotide diversity, and LD analysis indicated that the LVK population exhibits substantial levels of genetic diversity. LVK genome was dominated by short runs of homozygosity (ROHs, ≤ 500 kb) with a median length of 25 kb. With FROH 2.49%, average inbreeding levels were low; however, FROH ranged broadly from 0.13 to 12.2%. With the exception of one pure-blood breeding buck exhibiting FROH of 9.3% and FSNP of 8.5%, animals with at least 66% LVK ancestry showed moderate or no inbreeding. Overall, this study demonstrated that the LVK goats can be differentiated from imported breeds, although the population has a complex genetic structure. We were able to identify potential genetic traits associated with SCC levels, although the kinship of the animals and the heterogenic substructure of the population might have largely influenced the association analysis. We identified 26 genetic variants associated with SCC levels, which included the potentially relevant SNP rs662053371 in the OSBPL8 gene, indicating a potential signal linked to lipid metabolism in goats. To conclude, these findings present valuable insight into the genetic structure of the LVK breed for the conservation of local genetic resources.